Q: What is 6 X -3?

Write your answer...

Submit

Related questions

x - 6 - 3 = x -9

2x+6 = x+3 the x cancels out the other x x+6=3 subtract 6 from both sides x+6 -6 = 3 -6 x= - 3

if x+3=6then X= 6 - 36 - 3 = 3Remember that when we reverse the equasion we turn the + into a -.3+3=6Truex=3so x equals 3

18

2 x 3 is 6 / 6 x 6 = 36

x2+x-6=x2+3x-2x-6x2+x-6=x(x+3)-2(x-3)x2+x-6=(x+3)(x-2)

1, 2, 3, 6: 1 x 6, 2 x 3.

the fact family of the numbers 3, 6, and 18 is: 3 x 6 = 18; 6 x 3 = 18; 18 ÷ 3 = 6; 18 ÷ 6 = 3

If: x+6 = 3 then the value of x is -3

factors of 6 are: 1, 2, 3, and 6. 1 x 6=6, 2 x 3=6, 3 x 2=6, 6 x 1 = 6

6 x 1 = 6 3 x 2 = 6 6 x 2 = 12 3 x 4 = 12 6 x 3 = 18 3 x 6 = 18

x + 6 = 3Subtract 6 from each side:x = -3

Use various operations to isolate the variable. Here's an example: 0=5(3-x)2-6 6=(3-x)2 √6=3-x (√6)-3 = -x 3-(√6) = x

6 x 3 - 6 x 2can also be written as(6 x 3) - (6 x 2)where the multiplication is done first. Then you get18-12and that equals6

3*x+6 common factor of 3&6 is 3 divide both terms by three: 3*x/3 --> x 6/3 --> 2 3(x+2)

6 = 1 x 6, 2 x 3, 3 x 2, 6 x 1

1 x 6, 2 x 3, 3 x 2, 6 x 1

6,636 = (6 x 1000) + (6 x 100) + (3 x 10) + (6 x 1) or (6 x 10^3) + (6 x 10^2) + (3 x 10^1) + (6 x 10^0)

x+3/2=3 = x+3=6 = x+3(-3)=6(-3) = x=3

9

10 x 3 - 6 = 24 6/6 x 10 x 3 -6 = 24

In thing like: x+3=6 =6-3=x x=3

(9 - 6)! x 22 1: 9 - 6 = 3 2: 3! = 3 x 2 x 1 = 6 3: 6 x 22 = 6 x 2 x 2 = 24

If you mean 3 times 6 then it is 18

9 + x = 3 x = 3-9 x = -6 Check 9 + (-6) = 3 9 - 6 = 3